Distinctive quadrangular seed-bearing structures of gnetalean affinity from the Late Jurassic Morrison Formation of Utah, USA. (21st October 2021) - Manchester, Steven R.; Zhang, Xiaoqing; Hotton, Carol L.; Wing, Scott L.; Crane, Peter R.
Abstract : A new kind of seed-bearing structure is described based on three-dimensional casts and partially permineralized small cones from the Upper Jurassic Brushy Basin Member of the Morrison Formation, in the Henry Mountains of Utah. Cones of Dayvaultia tetragona gen. et sp. nov. are obovate in lateral view, 10.0–11.0 mm long, square in cross-section and 5.1–8.0 mm wide, with a thick wall composed of four tightly adhering bracts that open apically to expose the tips of six or eight elongate, four-lobed seeds. Micro-CT scanning reveals that the seeds are borne on a cup-shaped receptacle in a regular opposite and decussate manner. This regular arrangement, as well as similarities of the seeds to several kinds of Early Cretaceous chlamydospermous seeds, including those of Lobospermum and Battenispermum, suggests a relationship to extant and Cretaceous members of Gnetales. The sedimentary context in which the cones occur, combined with their local abundance, suggests that Dayvaultia was common on intermittently inundated well-drained floodplains during Morrison times, enhancing insight into the vegetation that supported the diverse vertebrate faunas for which the Morrison Formation is well known. http://zoobank.org/urn:lsid:zoobank.org:pub:0ECD4B37-E6B6-4050-B45A-28D713321EB8